Reactivity and Selectivity Principles in Native Protein Bioconjugation. Issue 8 (28th June 2021) - Adakkattil, Ramesh; Thakur, Kalyani; Rai, Vishal
Abstract: Are chemical methods capable of precisely engineering the native proteins? Is it possible to develop platforms that can empower the regulation of chemoselectivity, site‐selectivity, modularity, protein‐specificity, and site‐specificity? This account delineates our research journey in the last ten years on the developments revolving around these questions. It will range from the realization of chemoselective and site‐selective labeling of reactivity hotspots to modular linchpin directed modification (LDM®) platform and site‐specific Gly‐tag® technology. Also, we outline a few biotechnology tools, including Maspecter®, that accelerated the detailed analysis of the bioconjugates and rendered a powerful toolbox for homogeneous antibody‐drug conjugates (ADCs). Abstract : Protein bioconjugation is turning into a pivotal area that connects chemistry, biology, and medicine. In this direction, we have developed hotspot‐targeting methods, LDM® platform, and Gly‐tag® technology. We also established enhanced analytical tools such as Maspecter® to enable an unambiguous analysis of bioconjugates.